الجــامعــة والمجـتمــع "دور الجامعة في تدريب العاملين مع اطفال الشوارع" - سناني, عبد الناصر (جامعة الوادي - University of Eloued, 2020)
يؤكد " ايرون ساندرز" انه " لا يمكن للجامعة أن تعزل نفسها عن المجتمع الذي يدعمها بل عليها أن تخدم ذلك المجتمع و إلا اعتبرت غريبة عنه و غير جديرة بالثقة التي أولاها إياه" من هذا المنطلق كيف للجامعة من تحسين مخرجاتها من الكوادر و في نفس الوقت أن تكون الجامعة فضاء تكويني من خلاله يتدرب العاملين مع هذه الفئة من الأطفال على أحسن و أنجع الوسائل و الطرق لضمان تكفل أحسن بهذه الفئة التي يطلق عليها "أطفال الشوارع". وهذا إيمان منا أهمية دور الجامعة في خدمة المجتمع وبتالي المشاركة الفعالة في تنميته. ظاهرة أطفال الشوارع مؤشر خطير في المجتمع و عنصر سالبا في التنمية المستدامة التي تنشدها المؤسسات الوطنية و المنظمات غير الحكومية بالتعاون مع الحكومات لضمان القضاء عليها ومنع تكرارها في هذه الورقة نحاول تقديم بطاقة فنية تتضمن كيفية تنمية و تطوير مهارات العاملين مع أطفال الشوارع (sdf)، حتى يتسنى لهم التعامل مع هذه الفئة الهشة وفق منهجية علمية تعطي نتائج أحسن و أفضل ،و لما لا التكفل التام بالطفل من حيث إعادة تأهيله من كافة الجوانب ثم عودته للأسرة أن أمكن، وأخيرا إدماجه في المجتمع و بدلا أن يكون عالة يصبح عنصر فعال في التنمية الوطنية لبلاده. Iron Sanders says, "The University cannot isolate itself from the society that supports it, but rather that it should serve this community." Otherwise, she is considered foreign to him and untrustworthy”.From this point of view, how can the university improve its production and at the same time be a training space through which the workers who are in relation thoseclose with these groups of children are trained in the most effective way for better deal with this category which is called `` street children ''. We are convinced of the importance of the role of the university in the service of the community and therefore of its effective participation in its development.The phenomenon of street children is a dangerous indicator in society and a negative component of sustainable development. National institutions and NGOs, in cooperation with governments, seek to guide and avoid their recurrence. In this article, we try to offer a training program (à la carte training) that includes how to develop the skills of workers with street children (sdf), so that they can manage this fragile group according to a scientific methodology that gives better results,and his rehabilitation in all its aspects, and therefore his return to the family if possible, and finally his integration into society and instead of becoming a dependent, he becomes an effective element in the national development of his country. .
University And Society The University’s Role In Training Workers With Street Children
مقال
Keywords: خدمة المجتمع، التدريب، العاملين، أطفال الشوارع، البرنامج; university, Community Service, training, workers, street children, program.